Description of preterm neonates admitted and readmitted in Spain: causes and cost - Juliana de Jesus Alves; Maria Dolóres Redín Areta; Blanca Marín Fernández (Universidad de Alicante, 2019)
Objective: Identify the primary cause of the hospital admission and readmission of premature infants and evaluate the costs of the readmission between the years 2000 and 2011 in the Comunidade Foral de Navarra hospital in Pamplona, Spain. Methods: This is a descriptive, retrospective study involving analysis of 297 premature infants who were admitted to the neonatal Intensive Care Unit and were subsequently readmitted at another division of the aforementioned hospital, at least once, during the sixty days after discharge. Results: The majority of the cases studied (91.25%) were re-hospitalized only once, with an average stay of 4.61 days. Bronchiolitis and asthma were the most common cause for patient readmission. Conclusion: The author highlights the importance of parental presence during the child's hospitalization, as they can provide detailed information on the normal characteristics of their child and the potential health issues associated with prematurity. If the child presents any symptoms, the parents will know to seek medical help in the early stages, reducing the risk of complications and future hospitalizations.